(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to find out the effect of the project’s learning strategy on developing creative thinking among female students of the Institute of Fine Arts in the subject of interior design. To achieve the goal of the research, the researcher used a one-group experimental design with a pre- and post-test for creative thinking to suit it on a sample of third-grade students from the Institute of Fine Arts. Statistics, including; The Wilcoxon test for one sample to show the results of the research, the Keoder-Richardson equation / 20 and the t-test for two independent samples (to calculate the stability of the creative thinking test) Cohen’s equation to measure the effect size of the gradual change strategy Spearman’s corrective equation to correct the correlation coefficients for the purposes of stability. The most important results of the study showed: 1- The project’s learning strategy has had an impact on developing creative thinking among the female students of the Institute of Fine Arts in the subject of interior design. The digital educational environment has contributed to increasing the skill performance scores of the students of the experimental group. 2- There is a very high difference between the two responses, before and after, on the scale of creative thinking for female students of the Institute of Fine Arts in the subject of interior design. Based on the findings of the study, the researcher recommended several recommendations, including: Directing the faculty in the interior design departments to increase interest in providing enrichment and guidance programs for female students that contribute to the development of creative thinking. To complement the current research, the researcher suggested several proposals, including: 1- The impact of the project’s learning strategy on developing the skills of art education students in sculpture.